Enhanced stability and controlled gastrointestinal digestion of β-carotene loaded Pickering emulsions with particle–particle complex interfaces. Issue 21 (7th October 2021) - Wei, Yang; Zhang, Liang; Liao, Wenyan; Mao, Like; Zhang, Mengke; Guo, Xiaodong; Huang, Cancan; Han, Haizhen; Mackie, Alan; Gao, Yanxiang
Abstract : We used large, rigid, and hydrophilic zein-propylene glycol alginate composite particles (ZPCPs) and small, soft, and hydrophobic whey protein microgel (WPM) particles to synergistically stabilize a Pickering emulsion for delivery of β-carotene. Abstract : In this study, we used large, rigid, and hydrophilic zein-propylene glycol alginate composite particles (ZPCPs) and small, soft, and hydrophobic whey protein microgel (WPM) particles to synergistically stabilize a Pickering emulsion for delivery of β-carotene. The photothermal stability and storage stability of β-carotene were improved with the combined use of different particles. Microstructural observations showed that ZPCPs were effectively adsorbed at the oil/water interface despite the substantial interparticle gaps. WPM particles could swell and stretch on the interface due to their deformable structure, thereby forming an interfacial layer of flattened particles to cover a large surface area. The interfacial structure and macroscopic properties of Pickering emulsions were modulated by adjusting the mass ratio and addition sequence of different particles. The combination of ZPCPs and WPM delayed the lipolysis during gastrointestinal digestion. Through controlling the composition of the complex interface, the free fatty acid (FFA) release rate of Pickering emulsions in the small intestinal phase was reduced from 15.64% to 9.03%. When ZPCPs were used as the inner layer and WPM as the outer layer and the mass ratio of ZPCPs to WPM was 4 : 1, the Pickering emulsion showed the best stability and β-carotene bioaccessibility. The Pickering emulsion with particle–particle complex interfaces could be applied in foods and pharmaceuticals for the purpose of enhanced stability, delayed lipolysis or sustained nutrient release.